STRATEGI PEMERINTAHAN DAERAH DALAM PERCEPATAN PELAKSANAAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Dia Nursadiyah; Fernandes Simangunsong (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Buton, 2022)
This study seeks to analyze the strategy of local government in accelerating the implementation of integrated sub-district administration services (PATEN), as well as analyzing the factors supporting and inhibiting local government strategies in accelerating the implementation of integrated sub-district administration services (PATEN), The theory used is the strategy theory from Shirley which explains that strategy has several determining factors, namely Goals and Objectives, Environment, internal abilities, competencies, strategy makers, and communication. The research method used is descriptive and inductive approach, the data collection techniques used are interviews, observation, and documentation, the informants are the Regent of Tanah Laut Regency, Chair of the DPRD, Regional Secretary, Assistant Regional 1 Government and People's Welfare, Head of the Regional Development Planning Agency, Head of the Regional Development Planning Agency. Human Resources Development Personnel Agency, Head of Government Division, Head of Sub-Division of Government Administration, Head of Sub-Division of Regional Administration, Pelaihari Sub-District, Takisung Sub-District, Jorong Sub-District, Secretary of Pelaihari Sub-District, Secretary of Takisung Sub-District, Secretary of Jorong Sub-District The results of the study explain that the Regional Government strategy in accelerating the implementation of integrated sub-district administrative services (PATEN) in Tanah Laut Regency has been going well but in the process there are still obstacles due to the lack of human resources in terms of quality and quantity and there are still people who do not understand regarding integrated sub-district administration services (PATEN).